Pemberdayaan Karyawan Dan Motivasi Terhadap KinerjaKaryawan Di Perusahaan Logistik - Pinandita, Mashita; Subandi, Subandi; Fahriza, Basri (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of the study is to find out the employees’ development and motivation towards the performance of PT. Transporindo Agung Sejahtera employees. The method used in the study was quantitative method. The data analysis technique was using the multiple linear regression. The population was taken as the samples from the company of 35 employees. The result shows that there is a positive and significant effect of employees’ development and motivation towards the performance of the company’s employees.